2016
DOI: 10.3389/fpsyg.2016.01574
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Love Is Associated with Enhanced Inhibitory Control in an Emotional Stop-Signal Task

Abstract: Purpose: This study explored whether romantic lovers differ in emotion-related inhibitory control capacity from those who are single.Methods: 88 healthy undergraduate college students participated in the study. Half were currently in love and in a romantic relationship (love group, LG), and half were single and had never been in a romantic relationship (single group, SG). Based on duration of romantic relationship (i.e., love duration), the LG were further divided into two subgroups: “early stage love” and “lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 82 publications
2
10
0
Order By: Relevance
“…In the present study, we duplicate our previous main finding ( Song et al, 2016 ). Individuals exhibited longer SSRTs for sad condition trials as compared with neutral condition trials, suggesting impaired response inhibition in response to sad facial expression processing, which indicated that sadness (despite being an emotion of low arousal), like other strong negative emotions, can disturb behavioral inhibitory control.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, we duplicate our previous main finding ( Song et al, 2016 ). Individuals exhibited longer SSRTs for sad condition trials as compared with neutral condition trials, suggesting impaired response inhibition in response to sad facial expression processing, which indicated that sadness (despite being an emotion of low arousal), like other strong negative emotions, can disturb behavioral inhibitory control.…”
Section: Discussionsupporting
confidence: 92%
“…The explicit eSST may have a better ecological validity than implicit eSST in some situations. In daily socio-emotional contexts, it is of great importance executing successful response inhibition over negative emotions in an explicit manner in order to form and maintain an intimate relationship especially in early stages of love ( Song et al, 2016 ). Neither “priming eSST” nor “implicit eSST” paradigms seemed to be able to properly simulate the situations where executing inhibition with emotions is processed intentionally at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations